2009
DOI: 10.1108/00242530910969794
|View full text |Cite
|
Sign up to set email alerts
|

Sociability and social interaction on social networking websites

Abstract: Purpose -Social websites have become a major medium for social interaction. From Facebook to MySpace to emergent sites like Twitter, social websites are increasing exponentially in user numbers and unique visits every day. How do these websites encourage sociability? What features or design practices enable users to socialize with other users? The purpose of this paper is to explore sociability on the social web and details how different social websites encourage their users to interact. Design/methodology/app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
76
0
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(87 citation statements)
references
References 5 publications
1
76
0
3
Order By: Relevance
“…Such sociability (which is promoted by social affordances in the CSCL environment) promotes greater and more socioemotional interaction. The study of Keenan and Shiri (2009) supported the relationship as they linked the sociability of four social media applications (Facebook, Myspace, LinkedIn, and Twitter) with the high degree of social interaction that these applications facilitated. Charlton, Devlin, Marshall, and Drummond (2010) explored the influence of a status awareness tool called CommonGround on the degree of social interaction that is happening in a virtual team consisting of students collaborating with industrial clients.…”
Section: Sociability Influences Social Interaction (H S-si )mentioning
confidence: 86%
See 1 more Smart Citation
“…Such sociability (which is promoted by social affordances in the CSCL environment) promotes greater and more socioemotional interaction. The study of Keenan and Shiri (2009) supported the relationship as they linked the sociability of four social media applications (Facebook, Myspace, LinkedIn, and Twitter) with the high degree of social interaction that these applications facilitated. Charlton, Devlin, Marshall, and Drummond (2010) explored the influence of a status awareness tool called CommonGround on the degree of social interaction that is happening in a virtual team consisting of students collaborating with industrial clients.…”
Section: Sociability Influences Social Interaction (H S-si )mentioning
confidence: 86%
“…Thus, the different affordances may lead to differences in perceived sociability. Indeed, Keenan and Shiri (2009) found that Facebook, Myspace, LinkedIn, and Twitter differ in their sociability because of their particular affordances for social interaction. Oksanen and Hämäläinen (2012) found in a comparison between two different kinds of CSCL environments that "the level of perceived sociability was largely higher in serious game setting [i.e., 'Game Bridge'] than in the more traditional, asynchronous type of virtual environment" (p. 364).…”
Section: Social Affordances Influence Sociability (H Sa-s )mentioning
confidence: 99%
“…It features on the spot editing of the photos to share and upgraded to share videos as well (Kuppuswamy and Narayan, 2010). YouTube is also part of it where people share thousands kind of videos and it is used together with other social applications for a longer length of videos (Keenan and Shiri, 2009). …”
Section: Social Mediamentioning
confidence: 99%
“…It has transformed the way human interacts and expanded the boundary of communication in terms of contents and contexts. With the growth of social media, its influence is also expanded beyond personal communication, and its impact can be obviously seen in the way business operates (Keenan & Shiri, 2009). Since the advent of social media, many studies have explored its effects on the whole spectrum of human interaction and more are moving towards exploring its impact on business (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…LinkedIn is a business networking site that focuses on professional users creating and building a network of colleagues and other business connections (Keenan and Shiri, 2009). It has a clean and professional design, and is perhaps the site with the least (if any) potential for social interactions (OMurchu et al, 2004).…”
Section: Linkedin As a Social Networking Sitementioning
confidence: 99%